Efektivitas Gugatan Warga PTUN dalam Menguji Legalitas PBG Star Padel Pulomas - Oktavianus Abrianta Sembiring (Jurnal Litigasi Amsir, 2026)
This study examines community control mechanisms over State Administrative Decisions (KTUN) in the licensing sector through a case study of a citizens' lawsuit against the issuance of a Building Approval (PBG) for the commercial padel court "Star Padel" in the residential area of Pulomas, East Jakarta. Employing normative legal research with statutory and case approaches focused on PTUN Jakarta Decision Number 214/G/2025/PTUN.JKT, this research analyses: (1) the implementation of community participation in PBG issuance from the General Principles of Good Governance (AUPB) perspective; (2) spatial zoning compliance under DKI Jakarta's RDTR; (3) procedural failures in the electronic SIMBG verification system; (4) systemic implications of delegated authority violations; (5) post-verdict enforcement mechanisms; (6) environmental compliance obligations; and (7) access to justice constraints for affected citizens. The findings reveal that PBG Number SK-PBG-317502-24032025-003 violated multiple AUPB principles, contained procedural defects, including document manipulation, violated norms of delegated authority, and disregarded zoning regulations. The PTUN Jakarta panel granted the lawsuit in its entirety. This study confirms that citizens' lawsuits through the PTUN constitute an effective instrument of repressive control while functioning as an ultimum remedium in the face of preventive control failures.